ASTRO-ARCHAEOLOGY IN THE TRIANGULUM GALAXY: STUDYING GALAXY FORMATION AND EVOLUTION WITH THE GLOBULAR CLUSTERS AND STELLAR HALO IN M33 - Cockcroft, Robert (My University, 2012)
The currently-favoured cosmological paradigm, Lamda-CDM, predicts that galaxies are built up from smaller galaxies in a bottom-up process known as hierarchical merging. Lambda-CDM is extremely successful for large-scale structures, but is less so for the detailed features of individual galaxies. We can study these features - the galaxies’ foundations and the remnants of the smaller components that built them - only in the closest galaxies in which we can resolve individual stars. In this thesis, we use data from the Canada-France-Hawaii Telescope (CFHT)/MegaCam as part of the Pan-Andromeda Archaeological Survey (PAndAS) to observe M33 (the Triangulum Galaxy) and the detailed features of its old stellar population. The study of these details is vital for our understanding of galaxy formation and evolution. We search for two types of components within the old stellar population: globular star clusters and the faint, diffuse stellar halo. We find only one new unambiguous outer halo star cluster, in addition to the five previously known in the M33 outer halo (r=10-50 kpc). A further 2440 cluster candidates are identified, which we analyse using two different types of simulated clusters. We are able to describe the type of clusters that are likely to remain hidden from our searches. Our study of a population of red giant branch (RGB) stars far from the M33 disk reveals a low-luminosity, centrally concentrated component which we interpret as the discovery of M33’s halo. It is everywhere in our data fainter than mu_V ~ 33 mag arcsec^−2, with scale length r_exp ~ 20 kpc, an overall luminosity not more than a few percent of the total luminosity of M33, and is possibly also not azimuthally symmetric. For M33 to have so few outer halo clusters compared to M31 and to have such a low-luminosity halo, with the possible asymmetry that we see, suggests tidal stripping of M33’s halo components by M31 - a view that is also favoured by the morphology of the disk substructure and recent modelling.
Keywords: galaxies; evolution; halos; globular clusters; M33; Triangulum; External Galaxies; External Galaxies